MODULAR DESIGN AND ACTIVITIES OF STUDENTS IN THE FORMATION OF THEIR PROFESSIONAL AND RESEARCH COMPETENCIES. (Journal of Information Technologies in Education (ITE), 2013)
The article is devoted to coverage of the problems of using a modular design and technology training of students in creating their ability to research. Disclosed algorithm, organizational and pedagogical conditions for its implementation.
Keywords: research competence; self-search activity; self-study; module